1971
DOI: 10.1159/000466654
|View full text |Cite
|
Sign up to set email alerts
|

Automated Red Cell Antibody Analysis. A Parallel Study

Abstract: The AutoAnalyzer method of red blood cell antibody detection can be adapted to identify the serological specificity of these same antibodies. In the present study, 1,152 AA-positive sera obtained during AA screening were investigated. In 217 (19%) of these sera blood group antibodies were identified by manual techniques. Since the AA techniques are generally more sensitive than manual methods an attempt was made to identify antibodies by the AA methods in 823 sera which were negative manually. The low-ionic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
6
0
2

Year Published

1972
1972
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 18 publications
(27 reference statements)
2
6
0
2
Order By: Relevance
“…Experiments revealed that the LISPS system enhanced the reaction of MNS and Fya antibodies. Anti-K gave reactions equivalent to manual antiglobulin tests, but the system was slightly less sensitive than the BMC system in detecting weak anti-D, thus confirming the findings of Perrault and Hogman (1971).…”
supporting
confidence: 61%
See 1 more Smart Citation
“…Experiments revealed that the LISPS system enhanced the reaction of MNS and Fya antibodies. Anti-K gave reactions equivalent to manual antiglobulin tests, but the system was slightly less sensitive than the BMC system in detecting weak anti-D, thus confirming the findings of Perrault and Hogman (1971).…”
supporting
confidence: 61%
“…Habibi et al (1973) and Perrault and Hogman (1971) overcame this problem by utilizing a selected panel of donors, but the provision of sufficient fully typed fresh cells for antibody screening is often difficult. Marsh et al (1968) and Moore (1969) found that glycerol frozen cells failed to form satisfactory rouleaux in the BMC system, although Kolberg and Nordhagen (1975) have reported satisfactory results with frozen cells in this system.…”
mentioning
confidence: 99%
“…Marsh et al (1968) found that their BMC system reacted well with anti-S but anti-s was not tested. While Perrault and Hogman (1971) observed that the detection of anti-s on the AutoAnalyzer was less sensitive than the most appropriate manual technique. the anti-s described in this case was detected at a much higher titre on the AutoAnalyzer than by the indirect antiglobulin technique.…”
Section: Discussionmentioning
confidence: 98%
“…Graduell differierende D u -Antigene können auch dem Erfahrenen bei der Abgrenzung Iow grade D u /d, insbesondere aber bei der Differenzierung high grade D U /D erhebliche Schwierigkeiten bereiten (4,5). -Die kontinuierliche Durchflußanalyse ermöglicht durch die photometrische Agglutinationsmessung den objektivierbaren Nachweis abgeschwächt reagierender Blutgruppenvarianten (6)(7)(8). Wir berichten über eine technische Erweiterung des Technicon-Geräts Autogrouper 16 C, die die kontinuierliche Erfassung des D-Allels D u und weiterer Rh-Varianten der Loci C und E ermöglicht sowie über Beobachtungen bei der Analyse von abgeschwächten Varianten Rh-Faktoren der 3 Rh-Loci.…”
Section: Introductionunclassified